2011
DOI: 10.2196/jmir.1603
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Use of a Web-Based Application for Supporting the Self-Care of Patients with Type 2 Diabetes: A Longitudinal Study

Abstract: BackgroundThe take-up of eHealth applications in general is still rather low and user attrition is often high. Only limited information is available about the use of eHealth technologies among specific patient groups.ObjectiveThe aim of this study was to explore the factors that influence the initial and long-term use of a Web-based application (DiabetesCoach) for supporting the self-care of patients with type 2 diabetes.MethodsA mixed-methods research design was used for a process analysis of the actual usage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
217
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(235 citation statements)
references
References 67 publications
11
217
1
1
Order By: Relevance
“…Interactive eHealth tools designed to provide feedback on patients' self-monitoring appear to engage patients the most, since personalised and interactive features stimulate active participation by both the patient and the nurse. Nijland et al [35] reported that the diabetes patients in their study felt better monitored by the feedback they received and were therefore more motivated to take a more active role in the self-management of their illness, something that also led to increased independence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interactive eHealth tools designed to provide feedback on patients' self-monitoring appear to engage patients the most, since personalised and interactive features stimulate active participation by both the patient and the nurse. Nijland et al [35] reported that the diabetes patients in their study felt better monitored by the feedback they received and were therefore more motivated to take a more active role in the self-management of their illness, something that also led to increased independence.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies report that eHealth is promising with regard to selfmanagement support, and that people with chronic conditions desire tools that effectively reduce the limitations of life caused by disease [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…50 IHCAs have been investigated with relation to medication adherence for many chronic health conditions, including diabetes, hypertension, asthma, and cardiovascular conditions. [51][52][53] A recent review was conducted of IHCAs aimed at increasing adherence among the patients prescribed cardiovascular and diabetes medications. 50 This review …”
Section: Ihcas To Increase Patient Adherence To Medicationsmentioning
confidence: 99%
“…20 The first interesting outcome was that on average people logged on 49 times over 2 years with a progressively declining rate of engagement. The study observed that common barriers to sustainable engagement were:…”
Section: How Technology Can Leverage Patient Motivation and Improve Tmentioning
confidence: 99%